Du-lu ( m ) ki , Ar-mi ki (/Armānum), and Du-gu-ra-su ki (Tukriš) in the Ebla Documents - Archi, Alfonso (Orientalia, 2024)
The discovery at Ebla of some fragmentary objects inscribed with the names of Khafre (Dynasty IV) and Pepi I (Dynasty VI) suggests that relations with Egypt existed even in very early times. It has been proposed that Egyptian envoys likely reached Cilicia, where the city of Armi was supposedly located, and from there, established contact with Ebla. About one hundred proper names known from this city, half of which are Semitic, are documented at Ebla. This rules out Cilicia, which was never Semitized, as the location of Armi. Its identification with Old Akkadian Armānum strongly suggests that Samsat on the Euphrates is its location. Furthermore, the name Dugurasu, previously attributed to Egypt for this period, can only refer to Tukriš, an important state in the Transtigridian region that is well attested from the 3rd to the 1st millennium BC.